"Studying Land Cover Change in Habhab City Using Satellite Imagery and Geographic Information Systems" - Younis Majool , Assist. Lect . Zainab (Basra studies journal, 2026)
This study aims to analyze land cover changes in Habhab Subdistrict, located in Al-Khalis District west of Diyala Governorate, during the period 1994–2024. The analysis was conducted using satellite imagery (Landsat TM, ETM+, OLI, Sentinel-2) and Geographic Information Systems (GIS). Land cover was classified into three main categories: Green (agricultural/vegetated), Barren (unused lands), and Built-up (urbanized). The classification was performed using the Maximum Likelihood algorithm for supervised image classification. Results revealed a continuous decline in green areas from 34.1 km² to 14.5 km² (−57.5%), and a reduction in barren lands from 145.5 km² to 83.4 km² (−42.7%). Meanwhile, built-up areas significantly increased from 17.4 km² to 99.1 km² (+469.5%), reflecting rapid and unregulated urban expansion at the expense of agricultural and open lands. This study provides accurate spatial data to assist decision-makers in urban planning and environmental protection. It recommends strict regulation of urban sprawl and the rehabilitation of degraded agricultural lands.